Application of Defected Ground Structure for Augmenting High-Gain Ultra-Wide Bandwidth from Rectangular Microstrip Antenna. Issue 2 (17th February 2018) - Ankush, Pawar Umesh; Chakraborty, Subhradeep; Singh, L. Lolit Kumar; Chattopadhyay, Sudipta
ABSTRACT: The experimental investigations with hexagonal defected ground structure-integrated rectangular microstrip antennas show some interesting results on the input and radiation characteristics of a patch to the present authors. Unlike the earlier reports on implementation of defected ground structure in microstrip antenna for lowering only cross-polarized radiation, the present investigation shows that the bandwidth and the gain properties of such antenna can also be improved by judicious exploitation of the defect geometry on ground plane. Around 58% input impedance bandwidth (covering the whole Ku band) with high gain (around 9.1–9.4 dBi) and stable radiation pattern is obtained from the present structure.